Pedagogical conditions of using multimedia technologies in the process of teaching English at a non-language university under the conditions of distance learning - Berkutova, Tetyana Ivanivna; Vrakina, V. V.; Sadkovska, Valeriia A.; Shtuchenko, I. Ye. (Національний технічний університет "Харківський політехнічний інститут", 2023)
The article deals with the pedagogical conditions of using multimedia technologies in the process of distance learning of English for students of non-language higher educational institutions. The analysis of scientific sources on the study of the use of computer tools in the process of distance learning of a foreign language is carried out. The effectiveness of modern multimedia technologies in teaching English is substantiated and multimedia tools that significantly increase students' motivation and, as a result, the quality of their foreign language training are identified. The new possibilities of presenting educational material that open up to the teacher due to the introduction of multimedia resources into the educational process are highlighted. Considerable attention is paid to the role of feedback in ensuring effective interaction between student and teacher in the process of learning a foreign language in a distance format. It is noted that it is necessary to adhere to the principle of blended learning in the process of mastering a foreign language by students in the realities of distance learning, which also contributes to improving the quality and effectiveness of foreign language teaching. The most important pedagogical condition of distance learning of English is determined, which is the professionalization of training of future specialists. It is concluded that the digital format of multimedia technologies opens up new pedagogical opportunities for the organization of distance learning of a foreign language.

У статті розглянуто педагогічні умови використання технологій мультимедіа в процесі дистанційного навчання англійської мови студентів немовних вищих навчальних закладів. Проведено аналіз наукових джерел щодо вивчення питання застосування комп'ютерних засобів у процесі дистанційного навчання іноземної мови. Обґрунтовано ефективність сучасних мультимедійних технологій викладання англійської мови та визначено засоби мультимедіа, що суттєво підвищують мотивацію студентів і, як наслідок, якість їх іншомовної підготовки. Відокремлено нові можливості подання навчального матеріалу, які відкриваються перед викладачем завдяки впровадженню в учбовий процес мультимедіа-ресурсів. Значна увага приділяється ролі зворотнього зв'язку у забезпеченні ефективної взаємодії студента та викладача в процесі навчання іноземної мови у дистанційному форматі. Наголошується на необхідності дотримання принципу змішаного навчання в процесі опанування студентами іноземної мови в реаліях дистанційного навчання, що також сприяє підвищенню якості і ефективності навчання іноземної мови. Визначено найважливішу педагогічну умову дистанційного навчання англійської мови, якою є професіоналізація навчання майбутніх спеціалістів. Сформульовано висновок про те, що цифровий формат мультимедійних технологій відкриває нові педагогічні можливості для організації дистанційного навчання іноземної мови.
Педагогічні умови використання мультимедійних технологій у процесі навчання англійської мови в немовному зво під час дистанційного навчання
Keywords: multimedia technologies; distance learning; pedagogical conditions; competence; feedback; subject-subject interaction; мультимедійні технології; дистанційне навчання; педагогічні умови; компетенція; зворотній зв'язок; суб'єкт-суб'єктна взаємодія